Chest compressions for a patient in cardiac arrest after penetrating trauma with a knife still in situ. Issue 8 (25th July 2007) - McCarthy, Thomas; Lassota-Korba, Bozena; O'Leary, Tony; Knight, Richard; Murphy, Paul; Pandey, Rajesh
Abstract : A 45-year-old man was brought by ambulance to the emergency department. He was in shock, with a knife handle protruding from his abdomen. His pulse became undetectable. With the knife still in situ, external cardiac massage was provided on immediate transfer to the operating theatre. Resuscitation and haemostasis were achieved and the patient was eventually discharged from hospital. This case report discusses the risks of chest compressions for trauma patients with a penetrating weapon still in situ.